Sepsis in der Präklinik - Heim, Chiara; Genzwürker, Harald; Schmitt, Felix (Der Notarzt, 2025)
Sepsis is a life-threatening organ dysfunction caused by a dysregulated immune response to an infection. Approximately fifty million people develop sepsis every year, making it a common and relevant disease in emergency care. An early diagnosis and high-quality treatment can have a significant impact on the mortality rate. Therefore, disease awareness and knowledge concerning crucial steps in the diagnosis and treatment of sepsis are important for improving the prognosis of patients with sepsis. This article aims to summarize diagnostic steps and treatment recommendations for emergency medical services. Sepsis can present manifold, but certain symptoms of systemic inflammation should be recognized according to the qSOFA-score and the NEWS-2. If symptoms are observed, patients should be treated according to the ABCDE scheme. The most important treatment options in the prehospital setting include administration of O 2, fluid resuscitation and vasopressor therapy. If mechanical ventilation is necessary, medication should be chosen carefully according to the hemodynamic status of the patient. Prompt transport to an appropriate, specialized hospital and an early arrival and treatment are essential for effective prehospital sepsis management.